The Relationship between Self-efficacy, Resilience and Social Support with Relapse Tendency in Substance Use Disorder in Indonesia - Yanuarti, Tuty; Daud, Mohd Nazri Bin Mohd; Mohamed, Noor Hassline Binti; Atil, Azman Bin; Triaswati, Rusmai (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Substance use disorder (SUD) remains a major public health concern, with high relapse rates following detoxification treatment. Psychosocial factors such as self-efficacy, resilience, and social support may influence relapse outcomes, yet their roles remain underexplored in Indonesia. Objective: This study aimed to examine the relationship between self-efficacy, resilience, social support, and relapse tendency among Indonesians with SUD. Methods: A cross-sectional study was conducted at a rehabilitation center in Jakarta, Indonesia. Participants (n = 200; mean age = 37.56 ± 5.89 years) were adults (≥18 years) diagnosed with SUD by a psychiatrist. Standardized questionnaires assessed social support, self-efficacy, resilience, and relapse tendency. Correlation and mediation analyses were performed using bootstrapping with 5,000 samples (95% CI). Results: Social support was negatively correlated with relapse tendency (r = –0.42, p < 0.01), while self-efficacy and resilience were significant mediators in this relationship. The direct effect of social support accounted for 58% of the total effect, and the indirect effect through self-efficacy and resilience accounted for 37.34%. Conclusions: Higher social support reduces relapse risk, partly by enhancing self-efficacy and resilience. Strengthening these factors could be a key strategy in relapse prevention programs for Indonesians with SUD.